Perception of Teachers Regarding Role of STEAM Robotics Laboratories in Removing Boredom from Learning Science at the Elementary Leve - Kainat, Fozia Fatima, Sohaib Sultan, (JSE, 2023)
Educational technology is finding new ways to attain the attention of studentstowards science. One of the innovations in teaching science in the integrated classroom at STEAM robotics laboratories. The purpose of the research is toexamine the perception of teachers regarding the role of STEAM robotics laboratories in removing boredom from science classrooms.